In vitro loss of heterozygosity targets the PTEN/MMAC1 gene in melanoma - Robertson, Gavin P. (The National Academy of Sciences, 1998)
Gross genetic lesions of chromosome 10 occur in 30–50% of sporadic human melanomas. To test the functional significance of this observation, we have developed an in vitro loss of heterozygosity approach in which a wild-type chromosome 10 was transferred into melanoma cells, where there was selection for its breakage and regional deletion to relieve its growth suppressive effects. The overlap of these events was at band 10q23, the site of the recently isolated PTEN/MMAC1 tumor suppressor gene, suggesting it as a potential target. Although the gene was expressed in the parental cells, both of its chromosomal alleles contained truncating mutations. In vitro loss of heterozygosity resulted in loss of the chromosomally introduced wild-type PTEN/MMAC1, and ectopic expression of the gene caused cell growth suppression. Thus, this approach identified PTEN/MMAC1 as a target in malignant melanoma and may provide an alternative means to localizing tumor suppressor genes.